A Study on the production system of Eastern Telecommunications Philippines, Inc. - Macabeo, Ailene Marie; Onggue, Noel Lyndon; Sanchez, Eduardo Jr; Tabuzo, Ma. Judith; Yap, James April G. (College of Engineering, 1985)
This study on the Electronic Workshop, Terminals Section, of Eastern Telecommunications Philippines, Inc. was conducted from January to March 1985. It endeavors to analyze the systems of the Terminals Section with the aim of identifying possible or existing problem areas and formulating alternative solutions to them. The methodology employed consisted of plant visits to conduct the following: (a) interviews with management, technicians; (b) direct observation of operations processes; (c) data extraction from ETPI forms using forms designed by the group; and (d) analysis of the system using methods taught in IE 51: Production Systems. The following problems, their suggested solutions,and the respective limitations were observed: (1) Work overload of EWS personnel. This stemmed from the practice of sending Terminals technicians on field duty, the absence of time standards and a comprehensive specialization scheme. This could be surmounted by prohibiting field work for Terminals personnel; employing the time standards derived in this study, and preparing a specialization scheme according to type of repair required. The limitations to this though are the danger of unfulfilled commitments to clients if the regular field personnel cannot handle the job, and the longer time required to trace unusual faults that may occur, respectively. (2) The inventory control system utilized was insufficient to the requirements of it. The lack of forecasts, haphazard reorder levels, and inability to monitor demand all created frequent stockouts that in turn created a machine backlog. This could be avoided by employing a fulltime inventory clerk utilizing the procedures outlined in this study. budget constraints will dictate the limitations of this. (3) Poor production planning decreased the Section productivity. Lack of forecasts and demand history, as well as over-reliance on instinctive production scheduling all contributed to an inefficient production planning system. To improve this situation, proper procedures as outlines in this study should be employed. However, these procedures will only be as effective as the data used is accurate. This brings us to the fourth problem. (4) The poor monitoring system presently in use creates confusion as to what data is available . Thus, the three problems above have no basis for solution readily available at hand. Proper utilization of forms, and addition of several new forms, presented in this study, should alleviate the situation. No great amounts of extra paperwork will be incurred by these forms. All the recommendations presented in this study require little capital outlay. It is suggested that the details of the implementation schedule should be left to the IE/LT, or to the AM/T.